Place of exercise in the prevention of cancer (2017)
The evidence is growing to support the role of physical activity during and after cancer treatment. Keeping active throughout the cancer journey can preserve or improve physical function and psychological well-being, reducing the negative impact of some cancer-related side effects. Regular physical activity also has a potential role in reducing risk of cancer recurrence and increasing survival. Promoting physical activity as part of cancer care is a cost- effective intervention for the patients. There is clear evidence that physical activity is a safe and effective means to prevent cancer as well as mitigate disease and treatment-related side effects in both patients and survivors. Therefore the purpose of this study is to emphasize on the benefits of physical activity on cancer patients and survivors to reduce an increased risk for recurrence and/or onset of additional co-morbidities, and premature mortality.